Quantifying assessment of American ginseng (Panax quinquefolius L.) main root bruising based on FEM - Jia, Pengcheng; Zhu, Guixuan; Chen, Junzhi; Wang, Dong; Tang, Han; Wang, Jinwu (Frontiers in Plant Science, 2025)
Precise numerical simulation technology enabled the capture of subtle deformations in the American ginseng internal structure, allowing for an accurate assessment of bruise extent. In this study, a bilayer constitutive model of the American ginseng main root was developed through reverse engineering. The model accuracy was validated by velocity, exterior bruise area, and internal bruise area, with the highest velocity error being 3.8 %. Experiments analyzed the dynamic mechanical response of the American ginseng main root during collisions at various drop angles (30°, 50°, 70°, and 90°) and with different contact materials (steel, rubber, wood, and PVC). The effects of various collision conditions on bruise volume and bruise resistance index of the American ginseng main root was examined. The results demonstrated that a greater drop angle results in a larger bruise volume. The maximum bruise volumes were 3583.26 mm3 for steel and 3062.19 mm3 for wood. At a 30° drop angle, the bruise resistance index of the American ginseng main root was 59.14 mJ mm-3 for rubber and 40.89 mJ mm-3 for wood. At a 90° drop angle, the bruise resistance index was 45.72 mJ mm-3 for rubber and 35.38 mJ mm-3 for wood. At the same drop angles, the bruise resistance index of the American ginseng main root was consistently higher when rubber was used as the contact material. This study provides a scientific basis for the design and optimization of harvesting machinery and its key components, with the objective of effectively controlling the American ginseng bruising problem.